PREFERENCES FOR THE ORAL CORRECTIVE FEEDBACK TYPES IN SPEAKING CLASSROOM: VOICES FROM MALE AND FEMALE UNIVERSITY STUDENTS - Zaky Dzulhiza Hawin Amalia; Endang Fauziati; Sri Marmanto (Proceeding of International Conference on Art, Language, and Culture, 2019)
Oral Corrective Feedback (OFC) in language classrooms has received considerable attention for the last few decades. However, most of the studies focus on teachers’ practices, and how learners perceive these practices still needs investigation. Based on this, the current studyaims atinvestigating the male and female students’ preferences on thesix types of oral corrective feedback as proposed by Lyster and Ranta (1997), and revealing their underlying reasonbased on their preferences. This study was qualitative study. A set of questionnaires wasdistributed to a random sample of thefirst-year university students (15 males and 15 females), and interview was providedas the follow-up activity from the result of questionnaires. The result from the survey indicates that most of the male students have a higherpreference to explicit correction and most of the female students have a higher preference to metalinguistic feedbackcompared to other types of OCF. Furthermore, there are some reasons behind their choice of OCF types.They perceived that clarification request is the most ambiguous type to be comprehended,whereasexplicit correction and metalinguistic feedback are the easiest way to be recognized.  Theresult of this studyaims to improve the practice of oral correctivefeedback in speaking classroom.